Aging and older adulthood - Erber, Joan T. (Chichester, West Sussex : Wiley-Blackwell, 2013)
'The third edition of this essential text has been updated and expanded with new material that reflects the most recent developments in the field, and explores our current understanding of a broad range of topics related to aging and older adulthood. -Fresh edition includes updated content such as revised case histories and reworked material on key concepts and research applications -Retains the winning format of the second edition, with chapter contents framed by individual histories -Dual models add cohesiveness to the presentation of theory -Thematic structure facilitates reader comprehension -Instructor resources provided online upon publication at www.wiley.com/go/erber'--
Includes bibliographical references and index.
Keywords: Aging -- Research; Older people -- Research; Gerontology